Attitudes and Perceptions of Teachers and Students towards Environmental Education in Schools Surrounding University of Eldoret, Uasin Gishu County, Kenya - Nguru , N. M.; Odenyo , V. A. O.; Ouma , Odero D. (African Journal of Education,Science and Technology (AJEST), 2014)
The study investigated the attitudes and perceptions of teachers and pupils towards environmental education in schools surrounding University of Eldoret, Uasin Gishu County, Kenya. It aimed at finding out the level of knowledge on environmental education, modes of delivery and strategies of improving environmental education in the schools. It was carried out in the months of February and March 2014 during the first term of the primary school academic year. A survey research design was adopted, using questionnaires as the instrument for data collection. A Likert scale was used to measure attitudes, perceptions and level of knowledge.Schools were categorized into two: public and private, from each of which three schools were selected by simple randomization. Thus a total of six schools, thirty teachers and thirty six pupils from classes seven and eight participated in the study. Closed- and open-ended items in the questionnaire were used to collect data.. The relationship between respondents‟ environmental knowledge and their attitudes towards environmental education was determined by using simple Pearson correlation analysis. The study found that pupils had positive attitudes towards environmental education with a higher percentage of pupils in public schools strongly agreeing with the statement that learning about the environment is important, prepares pupils for the future and improves people‟s understanding and awareness of environmental issues. Private school teachers showed more positive attitudes than those from public school, and there was a significant positive relationship between attitudes and level of knowledge. Class instruction method was found to be the most used mode of delivery while a majority felt that field visits would be the best mode. One third of the interviewees suggested that more outdoor activities would improve teaching and learning of the environment and environmental issues.